Nanowires: Enhanced Optoelectronic Performance of a Passivated Nanowire‐Based Device: Key Information from Real‐Space Imaging Using 4D Electron Microscopy (Small 17/2016). Issue 17 (May 2016) - Khan, Jafar I.; Adhikari, Aniruddha; Sun, Jingya; Priante, Davide; Bose, Riya; Shaheen, Basamat S.; Ng, Tien Khee; Zhao, Chao; Bakr, Osman M.; Ooi, Boon S.; Mohammed, Omar F.
Abstract : Selective mapping of surface charge carrier dynamics of InGaN nanowires before and after surface passivation with octadecylthiol (ODT) is reported by O. F. Mohammed and co‐workers on page 2313, using scanning ultrafast electron microscopy. In a typical experiment, the 343 nm output of the laser beam is used to excite the microscope tip to generate pulsed electrons for probing, and the 515 nm output is used as a clocking excitation pulse to initiate dynamics. Time‐resolved images demonstrate clearly that carrier recombination is significantly slowed after ODT treatment, which supports the efficient removal of surface trap states.